Gold nanoparticles potentiate CaV channel currents in rat tail artery myocytes. (March 2018) - Fusi, Fabio; Sgaragli, Giampietro; Valoti, Massimo
Abstract: This study was designed to unveil effects of 5-nm sized, polyvinylpyrrolidone-coated gold nanoparticles (AuNPs) on vascular CaV 1.2 and CaV 3.1 channels. Ba 2+ currents through both channels (IBa1.2 and IBa3.1 ) were recorded in single myocytes isolated from the rat tail main artery by means of the whole-cell patch-clamp method. AuNPs increased IBa1.2 and IBa3.1 amplitude in a concentration- and Vh -dependent manner. Neither the voltage dependence of inactivation and activation curves nor inactivation and activation kinetics were affected by AuNPs. In conclusion, these findings warrant further investigation to clarify whether different types of NPs possess the same stimulatory activity and may represent a toxic hazard to humans. Highlights: The activity of AuNPs as vascular myocyte CaV channel modulators was assessed. AuNPs potentiated CaV 1.2 and CaV 3.1 channel currents. CaV current potentiation was concentration- and membrane voltage-dependent. Once demonstrated in vivo, these effects may explain the occurrence of vasoconstriction.